Early Cerebrovascular Autoregulation in Neonates with Congenital Heart Disease - Celina L. Brunsch; Mirthe J. Mebius; Rolf M. F. Berger; Arend F. Bos; Elisabeth M. W. Kooi (MDPI AG, 2022)
Neonates with congenital heart disease (CHD) display delayed brain development, predisposing them to impaired cerebrovascular autoregulation (CAR) and ischemic brain injury. For this paper, we analyzed the percentage of time with impaired CAR (%time impaired CAR) during the first 72 h after birth, the relation with clinical factors, and survival in 57 neonates with CHD. The primary outcome was a correlation coefficient of cerebral oxygenation (rcSO2) and mean arterial blood pressure (MABP, mmHg) for two hours on a daily basis. The %time impaired CAR ranged from 9.3% of the studied time on day one to 4.6% on day three. Variables associated with more %time impaired CAR were the use of inotropes (day 1, B = 19.5, 95%CI = 10.6-28.3; day 3, B = 11.5, 95%CI = 7.1-16), lower MABP (day 1, B = −0.6, 95%CI = −1.2-0.0), and dextro-transposition of the great arteries (dTGA) (16.2%) compared with other CHD types (2.0-5.0%; day 1, p = 0.022). Survival was not an associated variable. To summarize, impaired CAR was found in CHD neonates in up to 9.3% of the studied time. More evidence is necessary to evaluate an association with inotropes, dTGA, %time impaired CAR, and long-term outcome, further in larger cohorts.